Forecasting the Foreign Tourist Arrivals to Vietnam Using the Autoregressive Integrated Moving Average Method - TUNG, Le Thanh (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.v9.6(30).01, 2019)
The tourism has been recognized as the most important service sector in the economic development strategy of the Vietnamese government for the decades. The number of foreign visitors to Vietnam has increased rapidly over the years, however, the quality of the forecasting work has not met the requirements of the planning development. The serious over-loading of Vietnamese infrastructure as well as serving network has come by the problems in the forecasting. There is a large gap between the forecasting information and the real growth of the tourism sector in Vietnam. In order to solve this issue, our paper employs the ARIMA method to identify a more suitable tool for forecasting the foreign tourist arrivals to Vietnam. The data is used by the monthly form collected from the January 2009 to June 2018. The regression result determines the ARIMA (2,1,12) is the optimal model and applied to forecast the number of visitors come to Vietnam for three months of the third quarter in 2018.  Finally, our study result provides a useful forecasting tool for not only the Vietnamese policymakers but also the businesses in the tourism sector in Vietnam in the future.